2022
DOI: 10.1021/acschembio.1c00833
|View full text |Cite
|
Sign up to set email alerts
|

First Small-Molecule Inhibitors Targeting the RNA-Binding Protein IGF2BP2/IMP2 for Cancer Therapy

Abstract: The RNA-binding protein IGF2BP2/IMP2/VICKZ2/p62 is overexpressed in several tumor entities, promotes tumorigenesis and tumor progression, and has been suggested to worsen the disease outcome. The aim of this study is to (I) validate IMP2 as a potential target for colorectal cancer, (II) set up a screening assay for small-molecule inhibitors of IMP2, and (III) test the biological activity of the obtained hit compounds. Analyses of colorectal and liver cancer gene expression data showed reduced survival in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…To test whether violacein affects normal cells to the same extent, we used a model of long-term cultivation of Huh7 in human serum. The transition of the cell line towards a more normal, hepatocyte-like phenotype has been demonstrated previously ( 25 , 26 ). In this model, the activity of violacein was abolished ( Figure 1B ).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…To test whether violacein affects normal cells to the same extent, we used a model of long-term cultivation of Huh7 in human serum. The transition of the cell line towards a more normal, hepatocyte-like phenotype has been demonstrated previously ( 25 , 26 ). In this model, the activity of violacein was abolished ( Figure 1B ).…”
Section: Resultssupporting
confidence: 73%
“…Huh7 cells were differentiated in 2% human serum (PAN-Biotech #P40-2701) for three weeks, as described previously ( 25 , 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…These studies will be beneficial to assess whether IGF2BP3 can be targeted, e.g., by a decoy RNA or inhibitors, for the treatment of aggressive cancer. 31,32 Finally, while the present study focused on IGF2BP3, the IGF2BP family member that functions specifically in TNBC, it is worth to explore whether and how IGF2BP2 plays distinct roles in different subgroups of breast cancer. Since small molecule inhibitors for the components in the m6A methylation machinery are currently available, our findings hold out promise for development of novel therapeutics for clinical TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…462 In 2022, Dahlem et al reported that several ureidothiophene compounds target the RNA binding protein IGF2BP2/IMP2 [insulin-like growth factor 2 (IGF2) mRNA binding protein], which might be an interesting target in colorectal cancer therapy. 463…”
Section: Characterized Target Sites Of Rnap and Respective Inhibitorsmentioning
confidence: 99%
“…6B) inhibit the viral non-nucleoside reverse transcriptase of HIV-1 strains. 108 463 3.6.2. Sigma factor interaction inhibitorssummary and perspective.…”
Section: Sigma Factor Interaction Inhibitorsmentioning
confidence: 99%